Analisis dan Perancangan Sistem Informasi Manajemen Rantai Pasokan Perusahaan Pengelola Objek Wisata - Zauda Salma Salsabila; Izza Syahri Muharram; Muhammad Ainul Yaqin, (Jurnal Elektronika dan Teknik Informatika Terapan ( JENTIK ), 2024)
Integrated supply chain management is key in maintaining operational efficiency in the tourism sector, especially in high-demand tourist destinations such as Taman Ria. This research aims to analyze and design a Supply Chain Management Information System (SIMRP) that can integrate various elements of the supply chain at Taman Ria, from procurement, inventory management, to collaboration with suppliers. This research uses the Design Thinking method and Business Process Model and Notation (BPMN) to design a supply chain management information system that is effective and in accordance with user needs. The stages in Design Thinking that will be implemented include four main steps, namely empathize, define, ideate, prototype. The result of this research is that the implementation of the Supply Chain Management Information System (SIMRP) with the Design Thinking method and Business Process Model and Notation (BPMN) can effectively improve operational efficiency in tourist attraction management companies. With SIMRP, all processes from procurement, inventory management, to distribution can be automated and integrated into a unified system. This makes it easier for companies to monitor the flow of goods and information in real-time, so that decision-making can be done more quickly and based on accurate data. In addition, the involvement of BPMN in business process modeling enables a clear visual representation, making process identification and improvement easier.